2019
DOI: 10.1063/1.5092505
|View full text |Cite
|
Sign up to set email alerts
|

Rank reduced coupled cluster theory. I. Ground state energies and wavefunctions

Abstract: We propose a compression of the opposite-spin coupled cluster doubles amplitudes of the form τijab≡UiaVTVWUjbW, where UiaV are the nV-highest magnitude eigenvectors of the MP2 or MP3 doubles amplitudes. Together with a corresponding parameterization of the opposite-spin coupled cluster Lagrange multipliers of the form λabij≡UiaVLVWUjbW, this yields a fully self-consistent parameterization of reduced-rank coupled cluster equations in terms of the Lagrangian L0TVW,LVW. Making this Lagrangian stationary with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 91 publications
3
61
0
Order By: Relevance
“…The second approximation is the neglect of the L SVD 3 component in Eq. (35). We found that this term is numerically negligible in most cases, especially for smaller SVD subspaces.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…The second approximation is the neglect of the L SVD 3 component in Eq. (35). We found that this term is numerically negligible in most cases, especially for smaller SVD subspaces.…”
mentioning
confidence: 78%
“…However, these virtues come at a price of a rather steep scaling of the computational costs of the calculations with the system size. Therefore, many approaches such as optimized virtual orbital space, [9][10][11][12] frozen natural orbitals, [13][14][15][16] orbital-specific virtuals, [17][18][19][20] and local correlation treatments based on local pair natural orbitals [21][22][23][24][25] were proposed in the literature to alleviate this problem. Recently, a new idea to reduce the cost of CC (and related) methods has emerged which draws inspiration from the field of applied mathematics 26 and employs tensor decomposition techniques to the wavefunction parameters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sparsity of twoelectron repulsion integrals (ERI) can be utilized through the approximate decomposition over auxiliary basis sets obtained by density fitting, as in the resolution-of-identity (RI) methods [13][14][15][16][17][18][19][20][21], or by Cholesky decomposition of ERIs [22][23][24][25][26][27][28][29][30][31], or using alternative schemes such as pseudospectral decomposition [32][33][34], chain-of-spheres exchange [35][36][37], and tensor hypercontraction [38][39][40][41][42]. Decomposition of ampliomtudes can also be used to reduce computational costs [43][44][45][46]. A number of strategies exploit the physical decay of Coulomb interaction with a distance by using localized orbitals [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%